ANALISIS PENGGUNAAN DDC PADA SISTEM HVAC UNTUK MENINGKATKAN PENGHEMATAN KONSUMSI ENERGI DI HOTEL LANGHAM DISTRICT 8 SCBD JAKARTA - Wibisana Hadi Chandra; I.B Alit Swamardika; A.A Gede Maharta Pemayun (Program Studi Teknik Elektro UNUD, 2020)
Heating System, Ventilanting and Air Conditioning (HVAC) or air conditioning systemsbecome one of the needs in high rise buildings in order to increase comfort in the room,differences in the level of comfort of each individual makes the HVAC system changes in loadpatterns that can result in wasteful use of electrical energy. This study aims to determine thesavings in the use of electrical energy with the use of DDC in the HVAC system at the Langhamhotel. DDC can regulate HVAC system supporting devices such as cooling towers, condenserwater pumps, chilled water pumps and chillers that aim to reduce the performance of the chillersso that energy savings are obtained. By using 2 work operation methods, the results of thecalculation of energy use obtained at the side of the chiller Langham hotel, with manualoperation without the use of DDC obtained a total consumption cost of IDR 3,409,290 andautomatic work operations using DDC obtained a total consumption cost of IDR 2,601,990 sothat it is obtained saving percentage of 24%.